PENGARUH KEUNGGULAN PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA BENGKEL MOTOR BAMA DI TANJUNG DALAM KECAMATAN GUMAY TALANG KABUPATEN LAHAT - Hayani (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2022)
Based on the results of data processing, the regression equation Y = 4.666 + 0.092 + 0.808 The constant value of 4.666 means that if the independent variables are ignored or assumed to be zero, the value of the Consumer Satisfaction variable (Y) is 4.666 The value of the Product Advantage variable (X1) is 0.092 which means if the Product Advantage variable (X1) is increased by 0.092 it will increase the Consumer Satisfaction variable (Y) by 0.092. The value of the Service Quality variable (X2) is 0.808, which means that if the Service Quality variable (X2) is increased by 0.970, it will increase the Consumer Satisfaction variable (Y) by 0.808. The value of the terminated coefficient is 0.733, meaning that the independent variables have a contribution to the dependent variable of 73.3% and the remaining 26.7% is influenced by other factors not examined by the author. Adjusted R Square value of 0.329 means that the independent variables have a relationship with the dependent variable of 0.720. Testing the effect of the Product Excellence variable (X1) on Consumer Satisfaction (Y) with partial testing obtained the calculated value for the Product Excellence variable (X1) obtained a Sig value of 0.022, namely Sig 0.404 < 0.05 which means the Product Excellence variable (X1) has a significant effect on Satisfaction Consumers (Y), then reject Ho and accept Ha, so the hypothesis in this study is proven to show there is a significant effect of Product Excellence variable (X1) on Consumer Satisfaction (Y). Testing the influence of the Service Quality variable (X2) on Consumer Satisfaction (Y) with partial testing, the t_count value for the Service Quality variable (X2) obtained a Sig value of 0.000, namely Sig 0.000 > 0.05 which means that the Service Quality variable (X2) has no effect. Significantly on Consumer Satisfaction (Y), then accept Ho and reject Ha, so the hypothesis in this study is not proven to show a significant influence between Service Quality (X2) variables on Consumer Satisfaction (Y) The joint test shows a significant value of 0.000 meaning Sig 0.000 <0.05 then Ho is rejected and Ha is accepted. This means that the variables of Product Excellence (X1), and Service Quality (X2), have a significant effect together on Consumer Satisfaction (Y).